(untitled) (Research, Society and Development, 2020)
Assessments of teaching and learning styles are important parameters that determine the compatibility between student and teacher. Therefore, the objective of this work was to evaluate the teaching styles of teachers and the learning of students from the Technical Course in Automotive Maintenance Integrated to High School, from the Federal Institute of Minas Gerais, Campus Bambuí. For evaluation, the methodology was used, properly validated and identified by N-ILS (New Index of Learning Styles) composed of twenty questions. The questionnaire was prepared using an electronic form and made available, remotely, to teachers of technical disciplines and High School (9th grade; 10th grade and 11th grade) of the referred course. Subsequently, the data were tabulated in spreadsheets, and the teaching styles of teachers and students learning were classified. At the end, it was found that in the profile of teachers of technical disciplines of the integrated course in Automotive Maintenance, sensory perception, visual input, active processing and sequential understanding predominated. For the students, it was observed that they have a preference for sensory perception, visual input, reflective processing and sequential understanding. There was disagreement regarding the processing style between teachers and students.